2020
DOI: 10.1016/j.lfs.2020.118408
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical elevated B-type Natriuretic Peptide (BNP) indicates endothelial dysfunction contributing to hypoxia susceptibility in healthy individuals

Abstract: Aims Baseline elevated B-type Natriuretic Peptide (BNP) has been found in high altitude pulmonary edema susceptible population. Exaggerated pulmonary vascular response to hypoxia may be related to endothelial dysfunction in hypoxia susceptible. We hypothesize that baseline BNP levels can predict hypoxia susceptibility in healthy individuals. Main methods The pulmonary vascular response to hypoxia was compared in 35 male healthy individuals divided into two groups based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Molecular docking simulation between the jRdRp and potential natural compounds was performed by Chimera-AutoDock Vina plugin setup to decipher the most interacting residues in the active site of jRdRp against reference molecules, as reported earlier 50 . Briefly, 3D structure of protein and potential bioflavonoids as ligand were subjected to minimization under the default parameters in structure minimization tool in UCSF Chimera-1.14 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking simulation between the jRdRp and potential natural compounds was performed by Chimera-AutoDock Vina plugin setup to decipher the most interacting residues in the active site of jRdRp against reference molecules, as reported earlier 50 . Briefly, 3D structure of protein and potential bioflavonoids as ligand were subjected to minimization under the default parameters in structure minimization tool in UCSF Chimera-1.14 47 .…”
Section: Methodsmentioning
confidence: 99%
“…One hypothesis may be that proBNP elevation may occur independently of myocardial stress. A recent study posits that subclinical BNP elevation may indicate endothelial dysfunction leading to impaired microvascular compliance and subsequently impaired adaptation to hypoxia in COVID-19 ( 14 ). It is unknown whether this may be the underlying mechanism of seemingly stochastic lung injury in COVID-19 and is not addressed by our study.…”
Section: Discussionmentioning
confidence: 99%
“…26 Whether elevated troponins and NT-proBNP result from direct myocardial injury or myocardial injury secondary to endothelial disruption and impaired microvascular compliance is unknown. 27 Recently, however, the MYSTIC study of microvascular dysfunction in COVID-19 found, in a small cohort, that indices of endothelial dysfunction, namely ADAMTS-13, a VWF protease, and VEGF-A, better predicted mortality compared with indices of myocardial injury. 13 In fact, ADAMTS-13 inversely correlated with COVID-19 severity.…”
Section: Article In Pressmentioning
confidence: 99%